TMOD-28. MYC OVEREXPRESSION DRIVES MEDULLOBLASTOMA FROM HUMAN NEUROEPITHELIAL STEM CELLS - Hutter, Sonja (Neuro Oncol, 2018)
Medulloblastoma (MB) is the most prevalent malignant brain tumor in children. Based on molecular genetic profiling, this disease can be classified into four major subgroups which display distinct clinical features. Group 3 MBs are associated with overexpression or amplification of the MYC oncogene and rarely show any mutations in the tumor suppressor protein p53. Patients with MYC-driven MB have a particularly high risk of recurrence and are associated with extremely poor prognosis. Thus, modeling MYC-driven MB is critical for the development and testing of potential new treatment approaches for these high-risk MBs. Here we show the first human MB model developed from human hindbrain neuroepithelial stem (NES) cells and induced pluripotent stem cell-derived NES (iPS-NES) by lentiviral overexpression of wild-type MYC. Following orthotopic transplantation into immunodeficient mice these embryonic cells generate aggressive brain tumors with high penetrance in the absence of p53 mutations. The MYC-driven tumors are comprised of poorly differentiated cells with high expression of the proliferation marker Ki-67. Tumors also express early neuronal lineage marker Tuj-1 (neuron-specific class 3 beta tubulin) and the transcription factor OTX2. All these features closely mimic those of human Group 3 MB. The establishment of these human MYC-driven MB animal models will facilitate the functional study of MB biology and testing of potential therapies.